Criminal responsibility, abnormal mental states, and the functions of expert medico-psychological evidence - James, Hazel (2005)
This thesis exammes the interaction of law and medico-psychology in homicide cases, where the defences of insanity and diminished responsibility in particular are raised. If the defendant's mental state is subject to scrutiny through the defences, then expert medico-psychological evidence is required, yet law and medico-psychology have very different understandings on the mind and very different roles with regard to assessing individuals. Expert medico-psychological evidence can be submitted in the consideration of criminal responsibility, when sentencing is concerned with whether prison or hospital is most appropriate, and for release decisions involving judgments about the defendant's potential risk and dangerousness. The examination of the interaction between law and medico-psychology incorporated three dimensions. First, an exposition of the respective theoretical positions of the two disciplines on the mind, detailing the pertinent legislative and common law rules. The second analysed the judicial interpretations of the medico-psychological terms and concepts contained in the substantive law, and in addition, the controls developed through judicial reasoning on the procedural role of the expert and the admission of expert testimony. Finally, the practitioners' perspective is explicated, which was obtained by conducting interviews with lawyers and medico-psychological expert witnesses. There are two facets to the research conclusions, which simplistically stated are: first, in terms of the interaction between law and medico-psychology, the law uses medico-psychological concepts and evidence in a symbolic manner to facilitate legal objectives. Secondly, the examination of the nature of the interaction through the three dimensions exposed the fundamental difference between the theoretical legal debates and the practitioners' perspective. Although the former normally informs legislative and reform discussions, it seems from this research that consideration needs to be given to all the dimensions in future reform debates.